Hepatic Visualization on DXA Scan: An Ancilliary Finding - Ayesha Zubair; Sana Munir Gill; Aamna Hassan (Journal of the Pakistan Medical Association, 2024)
Thalassemia major is a genetic haemoglobinopathy manifesting as severe anaemia, jaundice and hepatosplenomegaly. Due to altered iron metabolism and increased bone resorption it is associated with secondary osteoporosis manifested as decreased bone mineral density (BMD). Dual energy X-ray absorptiometry (DXA) is frequently performed for the diagnosis of secondary osteoporosis. Soft tissues are rarely visualized on DXA unless there is calcification involving those structures like nephro-, cholelithiasis or iatrogenic e.g. surgical clips. Hepatic iron deposition occurs in thalassemia due to repeated blood transfusions which leads to increased density of the liver resulting in visualization of liver on DXA scan. We present an interesting image of hepatic visualization on DXA performed for bone mineral density assessment in a patient with thalassemia major. Keywords: Thalassemia major, secondary osteoporosis, iron overload, liver, DXA.